Pipistrellus (Pipistrellus) kuhlii subsp. lepidus Blyth 1845 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Pipistrellus (Pipistrellus) kuhlii subsp. lepidus Blyth 1845 Synonyms: Pipistrellus (Pipistrellus) kuhlii subsp. canus Blyth 1863; Pipistrellus (Pipistrellus) kuhlii subsp. leucotis Dobson 1872; Pipistrellus (Pipistrellus) kuhlii subsp. lobatus Jerdon 1867; Pipistrellus (Pipistrellus) kuhlii subsp. vispistrellus Bonaparte 1837. Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Chiroptera - Family Vespertilionidae, pp. 451-529 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 1, Baltimore :The Johns Hopkins University Press on page 476, DOI: 10.5281/zenodo.7316519